Elemente der antiken Erzähltheorie - Feddern, Stefan (Narratologia, 2021)
This volume is the first to systematically analyze ancient narrative theory in German. The guiding principle is the theory that, although ancient authors like Aristotle were the forerunners of the modern categories of narrative theories, many concepts have been reinterpreted in the course of their reception. It is against this backdrop that this monograph identifies the specific features of ancient narrative theory.